Extended follow‐up of an antibiotic cycling program for the management of febrile neutropenia in a hematologic malignancy and hematopoietic cell transplantation unit. Issue 2 (20th December 2012) - Cumpston, A.; Craig, M.; Hamadani, M.; Abraham, J.; Hobbs, G.R.; Sarwari, A.R.
Abstract Background Febrile neutropenia is a common complication during treatment of hematological malignancies and hematopoietic cell transplantation. Empiric antibiotic therapy in this setting, while standard of care, commonly leads to microbial resistance. We have previously shown that cycling antibiotics in this patient population is feasible. This report provides long‐term follow‐up of cycling antibiotics in this patient population. Methods In a prospective cohort of hematological malignancy patients with neutropenic fever, we sought to evaluate the role of empiric antibiotic cycling in preventing antibiotic resistance. Antibiotic cycling was initiated in March 2002 and, until June 2005, antibiotics were cycled every 8 months (Cycling Period A). From July 2005 to December 2009, antibiotics were cycled every 3 months (Cycling Period B). The rates of bacteremia, resistance, and complications were compared to a retrospective cohort (Pre‐cycling Period). Results The rate of gram‐negative bacteremia decreased when compared to Cycling Periods A and B (5.3 vs. 2.1 and 3.3 episodes/1000 patient‐days, respectively, P < 0.0001), most likely owing to implementation of quinolone prophylaxis. The resistance profile of the gram‐negative organisms isolated remained stable over the 3 time periods, with the exception of an increase in quinolone resistance during the cycling periods. Gram‐positive bacteremia rates remained stable, but vancomycin‐resistant Enterococcus (VRE) increased significantly (0.1 vs. 1.0 and 1.6 episodes/1000 patient‐days, respectively, P = 0.005) during cycling periods. Mortality rates were comparable. Conclusions Antibiotic cycling for neutropenic fever was effectively implemented and followed over an extended time period. Gram‐negative resistance remained stable, but there is some concern for selection of resistant gram‐positive bacteria, specifically VRE. Although antibiotic cycling did not seem to cause resistance in our study, further study is necessary to clarify the effect of cycling on antibiotic resistance, patient outcomes, and hospital cost.